String C-groups of order 1024 - Gomi, Yasushi (Archīum Ateneo, 2018)
This paper determines the nondegenerate string C-groups of order 1024. For groups of rank 3, we use the technique of central extension of string C-groups of order 512. For groups of rank at least 4, we compute for quotients of universal string C-groups.